Are your firm's taxes set in Warsaw? Spatial tax competition in Europe - Karen Crabbé; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
Corporate tax rates in Europe have been falling rapidly; as a consequence tax competition within the EU is fiercer than in the rest of the OECD. This paper analyzes heterogeneity in corporate tax rate changes between EU-15 countries as a function of the proximity to the EU-10 new member states. The average corporate tax rate in the new member states has always been considerably lower than the average in the EU-15 countries. Their entry into the EU eliminated capital barriers, in principle allowing firms to locate in one of the new EU-10 with full access to the European Market. Our results indicate that EU-15 countries physically closer to Central-Europe experienced more tax competition. Next we use a spatial regression framework to more firmally test the hypothesis that distance to a low tax region affects countries' tax reaction functions.
Keywords: H25; H77; H39; 330; Spatial tax competition; Corporate taxes; fiscal reaction function; Unternehmensbesteuerung; Steuerwettbewerb; Betriebliche Standortwahl; EU-Erweiterung; Steuerreform; EU-Staaten (Osteuropa); EU-Staaten; Steuerwettbewerb